Exploring of two different equated instability resistance training programs on measure of physical fitness and lower limb asymmetry in pre-pubertal weightlifters - Raouf Hammami; Hadi Nobari; Werfelli Hanen; Javier Gene-Morales; Haithem Rebai; Juan C. Colado; Luca Paolo Ardigò (BMC, 2023)
Abstract Background Although previous research in pediatric populations has reported performance enhancements following instability resistance training, the effects of different volumes on measures of balance, strength and power and lower limb asymmetry remain unclear. Objective To compare the effect of two 8-week instability resistance training programs (IRT1: 2 sets x 8 repetitions, 20% one-repetition maximum (1RM); IRT2: 2 sets x 4 repetitions, 40% 1RM) in balance (center of pressure displacements), 1RM, single-leg jumps, and inter-limb asymmetry of prepubescent weightlifters. Methods Thirty-two male athletes (10.94 ± 0.47 yrs, 17.05 ± 0.14 kg/m2, and 6.44 ± 0.93% bodyfat) voluntarily participated and combined IRT (front and back squat, lunge, and deadlift) with their usual weightlifting training. Nonparametric tests evaluated the differences between pre- and post-intervention. Results Significant improvements were encountered in all the variables for both groups (effect sizes [ES] from 0.46 to 2.60), except the inter-limb asymmetry and the velocity of displacement of the center of pressure, which did not improve in IRT2. It is also worth highlighting that in the single-leg jumps and center of pressure displacements, whereas no significant differences were observed between IRT1 and IRT2 in the baseline, significant differences appeared in the follow-up measurements. Conclusion IRT combined with weight-lifting training improves prepubescent weightlifters' performance; therefore, strength and conditioning coaches may consider including unstable devices with low loads into an overall conditioning program and warm-ups for prepuberal male weightlifters to promote their physical fitness and potentially decrease inter-limb asymmetry. Trial registration This study does not report results related to healthcare interventions using human participants; therefore, it was not prospectively registered.